Uses of Natural Honey in Cancer: An Updated Review - Tahereh Eteraf-Oskouei; Moslem Najafi (Tabriz University of Medical Sciences, 2022)
Cancer was predicted as the leading cause of death and the most important obstacle to the increased life expectancy in the 21st century worldwide. The World Health Organization (WHO) estimated number of new cases of cancers in 2020 about 19 million, and this number is estimated to be more than 295300000 people up to 2040 (more than 55% increase during next 20 years). Standard treatments for cancer include surgery, radiotherapy, and chemotherapy. However, all of these methods have dangerous side effects, so researchers are more interested in finding novel and less risky therapies. In recent years, there has been a great deal of interest in the development of anticancer agents obtained from foods or natural products. The relative safety of natural and food-derived compounds makes them attractive alternatives to conventional cancer treatment drugs. As a result, the majority of people are advised to use complementary and alternative medicine to treat and prevent cancer. In recent years, honey, as a natural product, has attracted many researchers' attention as an alternative to conventional anticancer drugs. Natural honey has long been used as a medicine and nutrient and its beneficial effects on various diseases in animal and human models have been studied. It was found that it has a wide range of therapeutic properties, including antioxidant, antibacterial, antiviral, anti-fungal, anti-diabetic, anti-inflammatory, anti-hypertensive, antiarrhythmic, wound healing, and liver protection benefits. This article aimed to review the role of natural honey in the prevention and treatment of a number of important cancers and their subsequent complications.